Analysis of Strengthening Occupational Safety Culture at PT Pupuk Sriwidjaja Palembang from a Risk Communication Perspective: - - Bob INDIARTO; Puji LESTARI; Kholil KHOLIL (International Journal of Environmental, Sustainability and Social Science, 2025)
This study aims to analyze the strengthening of occupational safety culture at PT Pupuk Sriwidjaja Palembang (Pusri) from a risk communication perspective. The background of this research is based on the context of the fertilizer industry, which has a high level of risk related to the handling of hazardous chemicals, making the need for a strong safety culture crucial. Safety culture encompasses not only adherence to procedures but also the values, subjective norms, and behaviors of organizational members that are internalized as part of daily work. The research method used was a descriptive qualitative approach with a post-positivist paradigm, analyzing secondary data from company strategic documents, academic publications, and research reports using content analysis techniques. This approach allows for an in-depth understanding of risk communication strategies and the formation of a safety culture within the company. The study found that strengthening safety culture at PT Pusri was implemented through a five-stage program, starting from spreading awareness and establishing subjective norms to data-driven interventions, using structured, systematic, and proactive principles. Risk communication serves as the foundation for developing employee safety attitudes and behaviors, supported by the Theory of Planned Behavior (TPB). This approach effectively encourages active employee involvement, competency development, and the achievement of the goals of a culture of independent safety and “Zero LTI”.